Assessment of the feed additive consisting of endo‐1,3(4)‐beta‐glucanase and endo‐1,4‐beta‐xylanase (produced with Talaromyces versatilis IMI CC 378536) (Rovabio® Excel) for all poultry species, weaned piglets, pigs for fattening and sows for the renewal of its authorisation (Adisseo France SAS) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of the feed additive consisting of endo‐1,3(4)‐beta‐glucanase and endo‐1,4‐beta‐xylanase (produced with Talaromyces versatilis IMI CC 378536) (Rovabio® Excel) for the renewal of its authorisation as a zootechnical feed additive for all poultry species, weaned piglets, pigs for fattening and sows. The applicant provided evidence that the additive complies with the conditions of the authorisation. The FEEDAP Panel concluded that the additive in all its formulations remains safe for all poultry species, weaned piglets, pigs for fattening and sows, and remains safe for consumers and the environment. Regarding user safety, all the forms of the additive are non‐irritant to the eyes or skin. Rovabio® Excel LC2 and Rovabio® Excel LC are not dermal sensitisers. Rovabio® AP and Rovabio® Excel AP T‐Flex should be considered dermal sensitisers; therefore, exposure to these forms of the additive by dermal routes is considered a risk. All the forms of the additive are considered respiratory sensitisers; any exposure by inhalation is considered a risk. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.